La declaratoria de utilidad pública de la actividad minera en las comunas, comunidades, pueblos y nacionalidades indígenas - Toapanta Lanchimba, Isaac (2016)
My thesis work carried out is of transcendental importance for the peoples and nationalities of our country about "The declaration of public utility of mining activity in the communes, communities, indigenous peoples and nationalities", worked and developed carefully, the which the legal necessity to treat, given that it is producing some outrages against the territorial rights of the communes, communities, indigenous peoples and nationalities, starting with the protected collective rights well recognized in the Constitution is clear and international treaties, when we tried specifically, public utility in ancestral territories of indigenous communities, the free exploration and servitude of it, we are feeling a clear violation of the rights of the territories of the communes, indigenous peoples and nationalities, expressed in international instruments, which recognizes the rights of indigenous peoples and nationalities, and also expresses clearly that neither for mineral prospecting their lands should be tapped. This contradicts with the Mining Act in force in the art. 15 and 28 on the declaration of public utility and freedom of exploration, I am convinced that the reform of these items, will be articulated in terms of rights, as regards the administrative act of public utility, on communal land and freedom prospecting therei